Leadership Capacity Building: A Strategic Approach to Promoting Heritage Tourism in Perigi Village, East Lombok - Surayyal Hizmi; Jujuk Ferdianto; Ali Muhtasom; Supardi; Syarihudin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
From 2023 to 2024, a strategic initiative was carried out by the community service team of Politeknik Pariwisata Lombok to develop leadership capacity and revitalize cultural heritage tourism in Perigi Village, Limbungan, East Lombok. Twenty young adults were trained in organizational leadership and work skills through workshops to foster community-based tourism. The training included team collaboration, tourism management, product development, halal certification, and digital marketing. This initiative led to the establishment of a tourism awareness group (POKDARWIS), officially recognized by the East Lombok Tourism Office, and created an integrated management system for the tourism team in Perigi Village. Participants were encouraged to explore tourism potentials, especially in Limbungan Traditional Village, as tourist attractions by showcasing the history and customs of the Sasak Tribe. However, the sustainability of the POKDARWIS needs attention, particularly in terms of team communication, operations, participation, and market exposure. Therefore, the strategy implemented includes ongoing communication and monitoring through social media discussion groups and appointing responsible individuals for each division. With this strategy, it is expected that the management can work more actively and efficiently in developing tourism in Perigi Village.